Estimating Transfer Function of Below-Knee Prosthesis at Two Phases of Gait Cycle - Ismail, Mahmud Rasheed; Ghani, Imad Zuhair (Al-Nahrain Journal for Engineering Sciences, 2017)
The modern development in prosthetics field demand the evaluation of the dynamical behavior and automatic control .The key process in the design and implement of these devices is the determination of the model parameters inherited with the transfer function .In such complicated structures it is so difficult to evaluate transfer function analytically ,however experimental approaches can serve as a simple and effective tool for estimating transfer function and model parameters .In this regard computer software such as Matlab is used .System Identification SID refers to the method for estimating the system transfer function from experimental tests by using computer .In the present paper; SID method is employed for analyzing below-knee prosthesis leg .In order to simulate with the practical requirement for design and evaluation ,two phases of human gait are considered ,namely; swing phase and single support of stance phase .The validity of this method is firstly checked by applying it on clamped-clamped beam model where the required parameters are evaluated and compared theoretically (via modal analysis) and experimentally (via System identification) .It is found that ; the error in estimating the transfer function parameter of beam is not exceeded 6% . Then the transfer function of the prosthesis are estimated for two phases of gait cycle .It is found that; the estimated transfer function of the prosthesis leg is highly affected by the phase type of gait cycle , where ;the natural frequency highly increases, the static gain decrease for support phase as compared with the swing phase ,however the damping ratio does not affected .